(3EOGQI GdehGQO GdHTQjI (B:s (3eONd GSJQGJjLj (B/s - (3YHGS, SgjdI eMeOs ((3YeGf(B: s (3OGQ hGFd ddfTQ hGdJhRjY(B, s, 2006)
(3EOGQI GdehGQO GdHTQjI, GdESJQGJjLjGJ hGdJMOjGJ(B- (3JNWjW GdehGQO GdHTQjI hJMOjO GdEMJjGLGJ(B- (3JOab GdYed hJMdjd GdhXGFa hJUejegG(B- (3GSJbWGH GdehGQO GdHTQjI(B- (3GNJjGQ GdehGQO GdHTQjI(B- (3Jbhje COGA GdYGedjf(B- (3OhGaY GdYed(B- (3JOQjH GdYGedjf hJWhjQge(B- (3EOGQI GdegfICfXeI GdCLhQ hGdQhGJH hGdJYhjVGJ(B- (3Mbhb GdYGedjf hfXGe GdEfVHGW(B- (3GdYdGbGJ GdUfGYjI hGdfbGHGJ(B- (3EOGQI GdSdGeI GdegfjI hGdUMjI(B- (3fXe eYdheGJ GdehGQO GdHTQjI(B.s
Keywords: (3EOGQI GdCaQGOs; (3EOGQI GdehGQO GdHTQjIs